"A child with autism only has one childhood": main themes and questions for research from the "Digital Bubbles" seminar series. Issue 3 (18th September 2017) - Parsons, Sarah; Yuill, Nicola; Brosnan, Mark; Good, Judith
Abstract : Purpose: The purpose of this paper is to present an overview of the main messages and key questions for further research arising from the seven-seminar series entitled, "Innovative technologies for autism: critical reflections on digital bubbles", funded by the Economic and Social Research Council in the UK. Design/methodology/approach: A synthesis of the main ideas is presented, drawing on the presentations, discussions, participant feedback, and short papers from across the seminar series, which took place between November 2014-2016. Findings: There were many positive examples where technologies were positioned and used as facilitative "bridges" between ideas, communities, understanding, and experiences. Researchers and community stakeholders also emphasised the importance of taking different perspectives and working in stronger partnerships with each other. Four overarching research questions were developed from these themes to provide a roadmap for future research, relating to: responsible innovation, technology-enabled social interaction, learning and pedagogy, and engagement. Originality/value: The findings and methodologies produced by the Digital Bubbles seminar series, available on the project website (http://digitalbubbles.org.uk /) and in a series of short papers, provide a rich repository of state-of-the-art thinking in the field of autism and technology that is being utilised nationally and internationally in teaching and learning. This paper suggests some valuable future research directions and highlights the importance of establishing and maintaining multi-disciplinary research teams, with autistic people and their families at their core.